STRATEGI PROMOSI WISATA DESA “SITE MUSEUM GEOLOGI LEMBAH CISAAR” DI DESA JEMBARWANGI KECAMATAN TOMO KABUPATEN SUMEDANG - Riki Ahmad Ramdhani (JRPA - Journal of Regional Public Administration, 2025)
To find out the Promotion Strategy of Village Tourism “Site Geological Museum Cisaar Valley” in Jembarwangi Village, Tomo Subdistrict, Sumedang Regency, to find out the inhibiting factors of “Site Geological Museum Cisaar Valley” in Jembarwangi Village, Tomo Subdistrict, Sumedang Regency in the management of village tourism, to find out efforts to overcome these factors in “Site Geological Museum Cisaar Valley” in Jembarwangi Village, Tomo Subdistrict, Sumedang Regency in the management of village tourism. Where the method that researchers use is qualitative research methods. Qualitative research methods are often referred to as naturalistic methods because the research is conducted in natural conditions (natural settings) The results of qualitative research emphasize meaning rather than generalization. Qualitative research methods are defined as the means used by researchers to solve problems and find answers to their research questions. The Cisaar Valley Geological Museum site still faces challenges in image marketing because it does not yet have a slogan or tagline. Natural attractions are available, but the tracking path is not yet organized. Accessibility infrastructure is still inadequate, although basic facilities are available. In people marketing, there are no well-known figures directly involved, but support comes from researchers and students. The main obstacle to the promotion strategy is the lack of human resources in POKDARWIS and the lack of official training, which has an impact on social media management and tour guiding. The solution is to increase competence through training and technical coaching for managers and tour guides.